Phylogenetic systematics of Mesonauta Günther 1862 (Cichliformes: Cichlidae: Cichlinae). - Oliveira, Rianne Caroline de (2024)
Cichlids have evolved into models for studying the evolutionary history of Neotropical fish. Many authors attempted to recover the group's phylogeny using morphological and molecular data, presenting satisfying solutions across a wide range of genera. However, intrageneric relationships remain obscure in a number of genus, potentially complicating species delimitation. Mesonauta presents six distinct species that are highly valued by aquarists. Currently, there is no proposed phylogenetic relationship between its species; however, it has a wide geographic distribution and phenotypic variations, with the possibility of new species not yet described. Species of the genus were delimited using molecular and morphometric data from preserved and deposited species in ichthyological collections. From the six previously described species, COI delimitate different species, since two of them (Mesonauta egregius and M. guyanae) were not corroborated by delimitation analysis and two are putative new species, showing six different species: M. mirificus, M. festivus, Mesonauta sp. “Pantanal”, M. acora, Mesonauta sp. “Amapá” and M. insignis. The results showed a new basis for studies within the genus and further research is needed to understand the wide distribution of M. mirificus. Mesonauta's monophyly was tested and the relationships between species by constructing concatenated cladograms based on molecular characters (COI, 16S) using three phylogenetic methods, from which two main clades were recovered a new species of Mesonauta was described from the Amapá Grande river basin, based on morphological and molecular characteristics, in a region affected by the presence of mercury. This is the first step in investigating the molecular phylogeny of Mesonauta, which showed intrageneric relationships based on molecular data, enabled the description of a new species of the genus and provided information for future research on the evolutionary history of the group.